Issues of recruitment and maintaining high response rates in a longitudinal study of older hospital patients in England–pathways through care study. Issue 5 (October 1997) - Gregson, B A; Smith, M; Lecouturier, J; Rousseau, N; Rodgers, H; Bond, J
Abstract : STUDY OBJECTIVES: To describe and discuss the methods used to recruit and maintain an unbiased sample of older discharged hospital patients in a study of the process and outcomes of hospital care. DESIGN: Prospective longitudinal interview study of consecutive patients admitted to hospital over a 12 month period and followed up for six months. Interviews took place in hospital five days after admission, at home 10 days after discharge, and six months after admission. SETTING: Six hospital locations: three in the north of England and three in the south. PARTICIPANTS: People aged 65 and over admitted to hospital with a new stroke or fractured neck of femur, their significant other, and nursing staff caring for them. MAIN RESULTS: Of 3105 patients referred to the study, 2111 were eligible and 1671 (79%) were recruited. Recruited stroke patients were younger than those not recruited and rates differed between locations for both stroke and fractured neck of femur. By six months after admission 25% had died. Outcome data were obtained for 85% of the surviving patients. Patients who died were older and frailer before admission. Among survivors, outcome data for stroke patients were less likely to be obtained for men, those more able initially, and those who were married. Response rates to each interview differed according to respondent types. Interviews were more likely to be obtained with significant others than patients. Patients who were not able to be interviewed were older and frailer; significant others were less likely to be interviewed if the patients were younger and more able. CONCLUSIONS: High response rates can be achieved with very frail older people if strategies are adopted to maintain their interest and if self reported data are supplemented by interviewing significant others.